2002
DOI: 10.1053/eupc.2002.0239
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial septum pacing avoids the adverse effect of interatrial delay in biventricular pacing: an echo-Doppler evaluation

Abstract: IAD produces different left and right atrioventricular sequences in BVP. IASP combined with BVP, by resynchronizing both atria and ventricles, is able to avoid this adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In fact, it has been demonstrated that the adverse effect of interatrial delay in biventricular pacing may be avoided with interatrial septum pacing. 32 • In some studies, it has been shown that interatrial conduction time (IACT) measured by tissue Doppler echocardiography was more closely related to the PR interval than to the duration of the P wave. Furthermore, in patients with heart failure and wide QRS, IACT is frequently prolonged.…”
Section: Clinical Implications Of Interatrial Blocksmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, it has been demonstrated that the adverse effect of interatrial delay in biventricular pacing may be avoided with interatrial septum pacing. 32 • In some studies, it has been shown that interatrial conduction time (IACT) measured by tissue Doppler echocardiography was more closely related to the PR interval than to the duration of the P wave. Furthermore, in patients with heart failure and wide QRS, IACT is frequently prolonged.…”
Section: Clinical Implications Of Interatrial Blocksmentioning
confidence: 98%
“…Other techniques that may offer more exact and/or precise measurements are signal averaging P wave, 2-bidimensional echocardiography with time Doppler imaging, and intracardiac ECG measurement. 31,32 May the interatrial blocks be of first, second, and third degree…”
Section: How Do We Measure Interatrial Conduction Timementioning
confidence: 99%
“…IACT has been reported to be an important consideration when programming the optimal atrioventricular delay (AVD) in patients that require atrial pacing. (5) The importance of IACT has not been studied prior to, or after CRT, during atrial-sensed biventricular pacing.…”
Section: Introductionmentioning
confidence: 99%
“…Porciani et al [64] compared septal and RA appendage pacing in 29 patients. In this small, non-randomized cohort, a significant divergence between Doppler assessed left and right mechanical AV delays was found in conventional atrial pacing compared with septal pacing, but the study did not examine the net effect on LV performance.…”
Section: Performance Of Non-apical Pacing Sitesmentioning
confidence: 99%